(3fTQ GdeMGSf GdZGdjI aj aVd eTGjN GdUhajI Chdi GdebGeGJ GdYGdjIs - (3GdjGaYj , Yaja GdOjf YHO Gddg Hf CSYO Hf Ydj GdjGaYj Gdjefj, Yaja GdOjf,J (B768 (3g` s ((3Ndjd Hf SdGeI Hf CMeO Hf eDfS GdCPQYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CMjG HPcQg bdhH ChdjGFg s
(3GdfSNI HgG MhGTs
(3HBNQgG fHPI ddeDda ai PcQ TF ef GdETGQGJ GdJi MUdJ ai gPG GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B72 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B34s
Keywords: (3GdJGQjNs